Evolving a national preventive protocol for vertical transmission of group B streptococcus in a low-resource country: The culture-based approach - Abdulbaki, Mariam; Ijaiya, Munirdeen; Fadeyi, Abayomi; Adesiyun, Omotayo; Adeniran, Abiodun; Aliyu, Onozare; Jimoh, Abdulgafar (Libyan International Medical University Journal, 2019)
Objective: The study objective was to determine the role and applicability of the culture-based approach to Group B Streptococcus(GBS) screening and the effect on pregnancy outcome. Materials and Methods: This is a prospective cross-sectional study involving 166 consenting antenatal clinic attendees at 35–37 weeks' gestation using purposive sampling. All participants had vaginal and rectal swabs collected and cultured with the availability of culture results at the time of presentation in labor. All GBS-colonized mothers received intrapartum prophylaxis with parenteral antibiotics based on antibiotic sensitivity from the onset of labor or the rupture of membrane until delivery. Statistical analysis was conducted using SPSS software version 21.0, while P < 0.05 was considered statistically significant. Results: The GBS maternal prevalence was 7.8%, and culture-positive women had both vaginal and rectal colonization. Marital status (P = 0.002), multiple sexual partners (P =0.001), previous sexually transmitted infections (P = 0.013), and low socioeconomic status (P = 0.012) were significantly associated with GBS colonization. GBS isolates were 100% sensitive to ampicillin, all participants had a minimum of two doses of intrapartum prophylaxis with parenteral ampicillin, there was no maternal morbidity, and the vertical transmission of GBS was 0%. Conclusions: The culture-based approach and the culture-based maternal intrapartum prophylaxis prevented both maternal and neonatal complications from GBS. Establishing regional- and national-level preventive protocols will be a central strategy for the prevention.
Keywords: Group B Streptococcus; maternal sepsis; national protocol; neonatal sepsis; screening protocol; vertical transmission of infections